Poor anaerobic threshold and VO2 max recorded during cardiopulmonary exercise testing (CPET) prior to cytoreductive surgery in advanced (stage 3/4) ovarian cancer (AOC) is associated with suboptimal cytoreduction but does not preclude maximum effort cytoreduction. (17th February 2022) - Element, Keziah; Asher, Viren; Bali, Anish; Abdul, Summi; Gomez, Dhanny; Tou, Samson; Curtis, Richard; Low, James; Phillips, Andrew
Abstract: This study assessed Cardiopulmonary Exercise Testing (CPET) in predicting oncological outcomes, post-operative recovery and complications in advanced ovarian cancer (AOC) cytoreductive surgery. We reviewed all patients who had CPET prior to AOC cytoreductive surgery with evidence of upper abdominal disease on preoperative imaging at the University Hospitals of Derby and Burton (UHDB) between August 2016 and July 2019. Patients were stratified by AT and maximum VO2 levels. 43 patients were identified. AT showed no relationship with major complications. 100% of patients in the AT ≥11 group received R0 ( n = 21, 91.30%), or R1 ( n = 2, 8.70%) cytoreduction, whereas in the AT <11 group, only 75.00% achieved and R0 or R1 resection ( p = .02). Surgical complexity was higher in the AT ≥11 group ( p = .001) and the VO2 ≥15 group ( p = .0006). No other correlations were seen between AT or VO2 max and complications or readmissions. No difference in overall survival was seen if R0 resection was achieved. IMPACT STATEMENT: What is already known on this subject? CPET testing allows pre-operative assessment of functional capacity to generate variables that can be used as a risk-stratification tool for major surgery. Whilst CPET testing has been shown to predict morbidity in non-gynaecological surgery, it remains unproven in cytoreductive surgery for ovarian cancer surgery despite being increasingly utilised. What do the results of study add? Our data suggest that CPET testing does not predict complication rates or survival in AOC. Patients with poor CPET performance are more likely to receive suboptimal cytoreductive outcomes from surgery. What are the implications of these findings for clinical practice and/or further research? CPET results should not be used to discount patients from cytoreductive surgery further research should address the interplay with nutrition, haematological markers, neoadjuvant chemotherapy and CPET performance.